DISTRIBUSI KARAKTER DAN FAKTOR LINGKUNGAN PADA STATUS GIZI BALITA DESA KALIALANG KEMANGKON, PURBALINGGA - Sigarlaki, Herke (Jurnal Kedokteran YARSI, 2008)
Long lasting economic crisis has various impacts to the communitylife and recently malnutrition cases have been emerged and easily found in several regions of the country. There were approximately around 1.5 million children suffering from malnutrition in 2004, and more or less 150 thousand among them were predicted to be suffering from marasmus, kwashiorkor and marasmus-kwashiorkor. This study was carried out employing a cross sectional approach. The population selected was a group of children coming to the study site selected by non-random sampling method. Univariate and bivariate analyses were performed both manually and using computer based approach. It was observed that up to 6.59% children suffering from malnutrition and residing at Kalialang village, Kemangkon, Purbalingga came from parents with primary school education background. Similar parents? education background was also observed in 14.24% children suffering from under nutrition.